Cerita Beji Antaboga dalam wacana harmonisasi alam dan antaragama - Subaharianto, Andang; Murti, Ghanesya Hari; Cahyawati, Erna; Wardani, Dyah Purwita; Basuki, Imam (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
The Beji Antaboga tourist site provides a religious atmosphere full of tolerance by building various statues of religious symbols located in a forest in Banyuwangi. The harmony between humans and nature is very well maintained at this location. This nuance is supported by a fictional story that is believed by the local community, namely the Antaboga dragon. However, the place is fully taken care of by Hindus who are indeed attached to protecting the surrounding nature, and their commitment to guard several points of springs. This research aims to measure the inter-religious relations in the area and also to analyze the extent to which folklore as a discourse can be recontextualized as an effort to harmonize the bond of humans with nature. The research method used is qualitative, the first step applies the narrative structure of the story through actantial theory, the second is tracing the hypogram for the Antaboga story which dated back to Hindu’s teaching, and the last is looking at discourse as a power practice to recontextualize the harmonius reality. The finding shows Antaboga story is indeed to legitimise nature as the centre and not humans as the main actors.